ORGANIZATIONAL SUPPORT AND INNOVATION CULTURE AS DRIVERS OF JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN INAPORTNET UTILIZATION - Maria Sampe; Irsan Tricahyadinata; Heni Rahayu Rahmawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Global public sector digital transformation emphasizes that the success of technology-based systems is determined not only by infrastructure readiness but also by organizational factors and employee psychological conditions. The current literature shows inconsistencies in explaining how organizational support and innovation culture translate into digital performance, particularly in the context of highly regulated bureaucracies. This study aims to integratively examine the influence of organizational support and innovation culture on employee job satisfaction and performance in the use of Inaportnet at KSOP Class I, Samarinda. A quantitative explanatory approach was used with a census method on 54 employees and analyzed using partial least squares (PLS)-based SEM. The results indicate that organizational support and innovation culture significantly affect job satisfaction and performance, with job satisfaction acting as the main mediator. Theoretically, this study integrates social exchange theory and dynamic capabilities in the context of public sector digital transformation. The novelty of this study lies in the confirmation of psychological mediation mechanisms in a high-risk port organization, which tests the limits of the theory's application to digital bureaucracy.